The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1242/dev.01271
|View full text |Cite
|
Sign up to set email alerts
|

Cell interactions that affect axonogenesis in the leechTheromyzon rude

Abstract: The leech nervous system comprises a relatively simple network of longitudinal (connective) and transverse (segmental) nerves. We have followed the normal pattern of axon development in the glossiphoniid leech Theromyzon rude by immunostaining embryonic preparations with antibody to acetylated α-tubulin. The dependence of the normal pattern of axon growth on cells in the mesodermal (M) and ectodermal (N, O, P and Q)lineages was examined by selectively ablating subsets of these lineages in developing embryos. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
3
4
0
Order By: Relevance
“…3). The onset of Hau-cif6 and Hau-cif7 expression was consistent with previous observations of neuronal morphological differentiation (Braun and Stent 1989; Shain et al 2004). Expression of Hau-cif6 and Hau-cif7 was first detected in a pair of cells within developing segmental ganglia during stage 9 (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3). The onset of Hau-cif6 and Hau-cif7 expression was consistent with previous observations of neuronal morphological differentiation (Braun and Stent 1989; Shain et al 2004). Expression of Hau-cif6 and Hau-cif7 was first detected in a pair of cells within developing segmental ganglia during stage 9 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…3A, B). The location of the first pair of cells expressing Hau-cif6 and Hau-cif7 was similar to that of the first cell pair that undergoes axonogenesis in segmental ganglia of Theromyzon rude , another glossiphoniid leech (Shain et al 2004). Based on these observations, we concluded that Hau-if6 and Hau-if7 mark the differentiating and differentiated neurons.…”
Section: Resultsmentioning
confidence: 66%
“…Cell migration is of course important not only in adults, but also early in the life of the organism (Shain et al, 2004). Although details of control of cell migration may vary from one motile cell type to another within a given animal, and even for the same cell type under different conditions, basic features of cell migration appear to be conserved across species, with various mechanisms proposed to account for directional sensing including models in which excitation and inhibition work in dual combination (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is significant that NO can play a major role in control of growth cone movement and motility (Tornieri et al, 2007; Welshhans et al, 2007). Whether some of the interactions between growth cones that influence their movement (Shain et al, 2004; Baker et al, 2007; Baker et al, 2008) are also important for guidance of microglial migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on arguments that Aciculata, a modern polychaete clade including Nereididae, is most closely related to stem annelids [7,8], the nereidid nervous system may be little changed from an early, errant polychaete ancestor. Despite advances made in understanding adult annelid nervous systems, exceedingly few studies focus on their nervous system development, the notable exception being studies on leech (e.g., [9-11]).…”
Section: Introductionmentioning
confidence: 99%